Pemanfaataan Fear of Missing Out (FOMO) sebagai Strategi Pemasaran UMKM Kuliner di Kota Kupang - Septia Sakalini Dioh; Jappy P. Fanggidae; Taqwa Sultan (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2026)
Rapid advances in digital technology require Micro, Small, and Medium Enterprises (MSMEs) to be adaptable in their marketing strategies. Generation Z, as a group with a high internet penetration rate (around 70%), has given rise to the Fear of Missing Out (FOMO) phenomenon. This study aims to examine the implementation of the FOMO phenomenon as a marketing strategy among MSMEs and to analyze its effectiveness in enhancing product appeal and influencing purchasing decisions. The method used is a qualitative approach with case studies of SME operators who utilize social media as a promotional tool. The results show that the application of FOMO strategies through viral content, time-limited promotions, and the utilization of social media trends can increase the visibility of SME products and encourage consumer engagement. As a community development, FOMO has proven effective in driving of MSMEs in the digital market and improving people's purchasing decisions.